2016
DOI: 10.1161/circulationaha.115.016522
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Patients With Chronic Thromboembolic Pulmonary Hypertension

Abstract: C hronic thromboembolic pulmonary hypertension (CTEPH) is a rare complication of acute pulmonary embolism with uncertain prevalence, ranging from 0.4% to 9.1%. 1 Diagnosis is strongly associated with a history of acute venous thromboembolism (VTE). 2,3 It is caused by nonresolving fibrothrombotic obstructions of large pulmonary arteries, combined Background-Chronic thromboembolic pulmonary hypertension, a rare complication of acute pulmonary embolism, is characterized by fibrothrombotic obstructions of large p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
462
4
37

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 558 publications
(566 citation statements)
references
References 33 publications
32
462
4
37
Order By: Relevance
“…With a median follow up of 20 months, the mortality rate in the Mexican registry reported by Al-Naamani et al [11] was 28 %, which is consistent with the outcomes reported in other registries in developed countries that are enriched with more resources. Examination of the survival curve for the cohort diagnosed via right heart catheterization discloses a 2-year survival of about 80 %, consistent with the survival rate reported in the international (European countries and Canada) registry for non-operated patients, but more than 10 % lower compared to operated patients [12]. As 67 % of the Mexican patients were deemed operable, it is evident that surgical therapy will improve outcomes should it become available.…”
supporting
confidence: 76%
“…With a median follow up of 20 months, the mortality rate in the Mexican registry reported by Al-Naamani et al [11] was 28 %, which is consistent with the outcomes reported in other registries in developed countries that are enriched with more resources. Examination of the survival curve for the cohort diagnosed via right heart catheterization discloses a 2-year survival of about 80 %, consistent with the survival rate reported in the international (European countries and Canada) registry for non-operated patients, but more than 10 % lower compared to operated patients [12]. As 67 % of the Mexican patients were deemed operable, it is evident that surgical therapy will improve outcomes should it become available.…”
supporting
confidence: 76%
“…Less experience with PEA (44 cases in 17 years) at our center compared with that in Europe and the United States can be a cause of higher mortality (5/44, 11.4%) 31. We excluded patients >75 years from the indication for PEA because the BPA program was initiated at our institution based on its lower mortality rate after BPA 13.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is necessary for understanding the pathophysiology of the development, progression of CTEPH in order to implement effective therapeutic and diagnostic strategies to decrease mortality rates (34). Studies show that the long-term prognosis of operated patients is better than the outcome of not operated patients (35).…”
Section: Tab 5 Triple Combination Of Cteph Risk Factorsmentioning
confidence: 99%